2020
DOI: 10.1016/j.btre.2020.e00570
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on the biochar production techniques, characterization, stability and applications for circular bioeconomy

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
282
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(294 citation statements)
references
References 143 publications
5
282
0
7
Order By: Relevance
“…Either this type of decomposition reaction is irreversible (decomposition of starch, protein) or reversible (ammonium chloride decomposition, calcium carbonate). The advantages of this method include ease of use, less time taking, cheap price and large-scale manufacturing [ 84 ].…”
Section: Synthesis Of Carbon Dotsmentioning
confidence: 99%
“…Either this type of decomposition reaction is irreversible (decomposition of starch, protein) or reversible (ammonium chloride decomposition, calcium carbonate). The advantages of this method include ease of use, less time taking, cheap price and large-scale manufacturing [ 84 ].…”
Section: Synthesis Of Carbon Dotsmentioning
confidence: 99%
“…The strong sorption of organic pollutants on the carbonaceous materials could reduce their microbial degradation leading to high residues of the pollutants in the soil (Ding et al, 2020). Some studies also illustrated that BC showed the potential toxicity to microbes induced by the organic compounds on the BC (Zhu et al, 2017;Yaashikaa et al, 2020). These might be the potential possibilities for the PAHs and PAEs in CKBC and CKBM higher than those in CKN.…”
Section: Figure 2 | Tn and Nomentioning
confidence: 99%
“…Biochar is commonly produced from pyrolysis of animal manures, crop residues, grasses and weeds, wood biomass, sewage sludge and municipal solid waste at a temperature ranging from 200 to 800 ‱ C [161,162]. The unique physico-chemical and sorptive properties of biochar, such as large surface area, high porosity, dominance of negatively charged surface functional groups, high cation exchange capacity and long-term stability [163], make it highly recommended as an amendment for contaminated soils. Biochar amendments can immobilize positive Pb cations through electrostatic attraction, precipitation as Pb-phosphate, surface complexation, and increasing soil pH [24,87,90,94,95].…”
Section: Agro-food By-products and Wastes As Soil Amendments Of Biolomentioning
confidence: 99%